Bilingual Youth: Spanish‐speakers at the Beginning of the 21st Century. Issue 6 (June 2016) - Potowski, Kim
Abstract: Spanish is spoken by approximately 406 million people, making it the second most commonly spoken language in the world. A fair estimate is that approximately one‐third of this population is bilingual. This article focuses on Spanish‐speaking bilingual youth in a variety of sociolinguistic situations around the world, summarizing a sample of research in four broad areas – linguistic structure, family language policy, education, and identity – and points out areas for future research.